Immortalized Mouse Floxed Fam20c Dental Papillar Mesenchymal and Osteoblast Cell Lines Retain Their Primary Characteristics. Issue 11 (November 2015) - Liu, Chao; Wang, Xiaofang; Zhang, Hua; Xie, Xiaohua; Liu, Peihong; Liu, Ying; Jani, Priyam H.; Lu, Yongbo; Chen, Shuo; Qin, Chunlin
<x xml:space="preserve">Abstract</x> Fam20c is essential for the normal mineralization of dentin and bone. The generation of odontoblast and osteoblast cell lines carrying floxed Fam20c allele can offer valuable tools for the study of the roles of Fam20c in the mineralization of dentin and bone. The limited capability of the primary odontoblasts and osteoblasts to proliferate necessitates the development of odontoblast and osteoblast cell lines serving as substitutes for the study of differentiation and mineralization of the odontoblasts and osteoblasts. In this study, we established and characterized immortalized mouse floxed Fam20c dental papilla mesenchymal and osteoblast cell lines. The isolated primary mouse floxed Fam20c dental papilla mesenchymal cells and osteoblasts were immortalized by the infection of lentivirus containing Simian Virus 40 T‐antigen (SV40 T‐Ag). The immortalization of floxed Fam20c dental papilla mesenchymal cells and osteoblasts was verified by the long‐term passages and genomic integration of SV40 T‐Ag. The immortalized floxed Fam20c dental papilla mesenchymal and osteoblast cell lines not only proliferated at a high rate and retained the morphology of their primary counterparts, but also preserved the dentin and bone specific gene expression as the primary dental papilla mesenchymal cells and osteoblasts did. Consistently, the capability of the primary floxed Fam20c dental papilla mesenchymal cells and osteoblasts to mineralize was also inherited by the immortalized dental papilla mesenchymal and osteoblast cell lines. Thus, we have successfully generated the immortalized mouse floxed Fam20c dental papilla mesenchymal and osteoblast cell lines. J. Cell. Physiol. 9999: 2581–2587, 2015. © 2015 Wiley Periodicals, Inc.